Application of Reward and Punishment to Develop Disciplinary Behavior of Early Childhood - Saputri, Aulia Indah; Widyasari, Choiriyah (Early Childhood Research Journal (ECRJ), 2021)
Reward includes the process carried out by giving reinforcement (reinforcement) in the form of rewards, so that with the award it is expected that it will naturally arise positive behavior and continue to do it better in the future. So that with the award of children will be considered to play a role or useful and feel valued for their efforts that can raise their status. In other words, reward can be said as one of the steps taken by children to give an award to children who have done their job properly. By giving rewards children are expected to maintain and even improve the quality of their achievement in the future. Punishment also has an equally important role in shaping or improving children's attitudes. Punishment is performed by children to provide improvements to unsatisfactory behavior or achievement. With the punishment it is expected that the child is aware of the mistakes he made so that he can consider something that will be done next. Punishment is done to avoid unpleasant conditions by correcting or minimizing unfavorable behavior. Therefore, with the behavior accompanied by punishment, the behavior (negative) will be reduced and will not even repeat. Punishment is done to avoid unpleasant conditions by correcting or minimizing unfavorable behavior. Therefore, with the behavior accompanied by punishment, the behavior (negative) will be reduced and will not even repeat. Punishment is done to avoid unpleasant conditions by correcting or minimizing unfavorable behavior. Therefore, with the behavior accompanied by punishment, the behavior (negative) will be reduced and will not even repeat.     In overcoming this discipline required the existence of school rules, consistency and implementing school discipline and partnerships with parents. Sanctions must not be given emotionally and according to taste, but must refer to existing standards and rules and aim at educating. With these things discipline in the school can be upheld and restored. Children who have problems with bad behavior can be helped and restored. It is hoped that such steps and attitudes will have a major impact on conducive conditions so as to create good learning outcomes and more positive changes in children's behavior.